Advances in atmospheric water generation technologies. (1st July 2021) - Raveesh, G.; Goyal, R.; Tyagi, S.K.
Highlights: Water-energy nexus is crucial in deploying atmospheric water generation systems. Novel concepts are explored, including hybrid atmospheric water generation systems. Sorption technology has great potential as a viable and sustainable water solution. Critical issues in existing atmospheric water generation techniques are addressed. Performance and perspectives of the reviewed technologies are summarized. Abstract: The availability of freshwater is persistently changing, and the current trends indicate that it is declining very rapidly, both quantitatively and qualitatively around the globe. Therefore, the shortage of freshwater will pose the biggest threat to mankind, and hence, there is an urgent need to develop and demonstrate new and sustainable technologies to address the issue. Atmospheric water generation technologies, which generate water from the air, has been untapped so far and could be an emerging alternative to tackle this issue. However, these technologies have been energy-intensive, which actually limits their widespread deployment in the field. The performance of various technologies has been summarized and compared in terms of their important performance parameters, constraints and advancements. The technological solutions to some of the current issues, retarding the growth of these technology have also been identified and discussed. Further, it is found that the advancement of some of these technologies is still in the nascent stage, and could not emerge as an economically viable solution. Thus, there is immense scope to explore atmospheric water generation and transform it into a feasible futuristic solution to water scarcity. Therefore, this review aims to provide the technical insight to re-examine the available technologies, research gaps and scope for further advancements.